An update: is there a relationship between H. pylori infection and nonalcoholic fatty liver disease? why is this subject of interest? - Chen, Xingcen; Peng, Ruyi; Peng, Dongzi; Xiao, Jia; Liu, Deliang; Li, Rong (Frontiers in Cellular and Infection Microbiology, 2023)
Helicobacter pylori (H. pylori) infection is thought to impact various extragastric diseases, including nonalcoholic fatty liver disease (NAFLD), the most common chronic liver disease. Meanwhile, the pathogenesis of NAFLD needs further research, and effective treatment for this disease remains elusive. In this mini-review, we systematically enumerate and ponder the evidence demonstrating an association between H. pylori infection and NAFLD. Primarily, we delve into high-quality metaanalyses and clinical randomized controlled trials focusing on the association studies between the two. We also discuss clinical studies that present opposite conclusions. In addition, we propose a mechanism through which H. pylori infection aggravates NAFLD: inflammatory cytokines and adipocytokines, insulin resistance, lipid metabolism, intestinal barrier and microbiota, H. pylori outer membrane vesicles and H. pylori-infected cell extracellular vesicles. This mini-review aims to further explore NAFLD pathogenesis and extragastric disease mechanisms caused by H. pylori infection.